Recursos de información y documentación deportiva en Internet. - Ghent, Gretchen (Revista General de Información y Documentación, 2000)
The article studies sport information resources on the Internet: the use of search engines to find web sites and how to evaluate web pages according to their information value. It also provides a list of major portals and subject directories and of the main academic and association web sites on sport, as well as lists of group news and information on how to subscribe.
Keywords: Sports documentation; Access to information; Internet; Webs; Infor niation evaluation